2015
DOI: 10.1136/bcr-2014-208118
|View full text |Cite
|
Sign up to set email alerts
|

Pathological fractures in a patient with chronic lymphatic leucaemia without disease progression

Abstract: SUMMARYWe describe a case of a 59-year-old woman with a medical history of upper leg pain and chronic lymphatic leucaemia (CLL), with known diffuse bone marrow infiltration and without signs of lymphatic or extra-lymphatic disease activity on positron emission tomography CT (PET-CT). She presented with multiple fractures of the pelvis, sacrum and left proximal femur as a result of a low energy fall. During admission, she sustained a non-traumatic fracture of the right proximal femur. Pathological fractures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…[7][8][9] Some cases in literature have already described the presence of lytic lesions in patients affected by CLL, and one of them was previously described by our group. 10 In 11 on 22 cases of the literature, patients had the axial skeleton or proximal long bones involved [10][11][12][13][14][15][16][17][18][19][20][21] and in rare cases fractures were localized to the skull or facial bones. 17,22,23 Multiple fractures were reported in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Some cases in literature have already described the presence of lytic lesions in patients affected by CLL, and one of them was previously described by our group. 10 In 11 on 22 cases of the literature, patients had the axial skeleton or proximal long bones involved [10][11][12][13][14][15][16][17][18][19][20][21] and in rare cases fractures were localized to the skull or facial bones. 17,22,23 Multiple fractures were reported in 8 cases.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31] Like this one, other cases in the literature described pathological fracture due to CLL involving the spine and vertebral compression fractures. 16,19,29,30 Of note, in 13 reports symptomatic osteolysis was the first presentation of a CLL. The cases reported in the literature are summarized in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…13 Almost all of the previously reported cases of pathological fracture associated with CLL occurred in the presence of hypercalcemia and were associated with Richter’s transformation or multiple myeloma. 9-16…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Langenberg et al reported a patient who was hypercalcemic and did not show any signs of Richter's transformation or multiple myeloma on the bone marrow sample but still developed pathological fracture of the distal femur due to CLL. 13 Almost all of the previously reported cases of pathological fracture associated with CLL occurred in the presence of hypercalcemia and were associated with Richter's transformation or multiple myeloma. [9][10][11][12][13][14][15][16] Review of literature suggests that the exact pathophysiology of the pathological fracture in CLL is not known but may be secondary to locally released osteoclast stimulating factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation